DESCRIPTIVE TEXT: DEVELOPING MEDIA BY USING POP UP POSTER - Ade Aini Nuran; Yeni Erlita (BAHAS, 2020)
Abstract  This research was aimed to develop appropriate, interesting and attractive writing media in teaching descriptive text for tenth grade students. Due to the result in the form of product, this research was conducted by using Research and Development (R&D) design. In conducting this research, the procedures were gathering the data and information, conducting the need analysis, designing the first draft of media, revising the media, and producing the final product as the pop up poster. The instruments of collecting data were the combination of two strategies; interview and questionnaires. The interview and questionnaire result proved that the students need writing media. The product had been validated by the experts. The overall assessments are 92.8. It means that developing writing media categorized as relevant for tenth grade students.Keywords: Developing writing media, Descriptive Text, Research and Development (R&D), Popup Poster